Answer:
1.F
2.E
3.A
4.D
5.B
Step-by-step explanation:
Ax+By=C
1.x+y=3
x+-x+y=3+-x
(x+-x)+y=3+-x
0+y=3+-x
y=-x+3
2.x-3y=9
x-x-3y=9-x
(x-x)-3y=9-x
-3y=9-x
-3y=-x+9
(-3y÷-3)=(-x÷-3)+(9÷-3)
y=3x-3
3.10x-2y=20
10x-10x-2y=20-10x
(10x-10x)-2y=20-10x
-2y=20-10x
-2y=10x-20
(-2y÷-2)=(10x÷-2)-(-20÷-2)
y=5x-10
4.6x=12+2y
(6x-6x)=12-6x+2y
2y=6x+12
(2y÷2)=(6x÷2)+(12÷2)
y=3x-6
5.4x+16-8y=0
move the expression to the right hand-side and change its signs
-8y=-4x-16
change the signs on both signs of the equation
8y=4x+16
divide both sides of the equation by 8
y=1/2x+2
I hope it helps